Building health research capacity in Africa: the Einstein-Rwanda research and capacity building program - Gad Murenzi; Gallican Kubwimana; Fidel Rubagumya; Pacifique Mugenzi; Alex Buteera; Emmanuel Rudakemwa; Jonathan Ross; Tiffany Hebert; Adebola Adedimeji; Sabin Nsanzimana; Marcel Yotebieng; Joel Palefsky; et al. (BMC Global and Public Health)
Abstract The growing demand for healthcare services and the burden of diseases such as cancer in sub-Saharan Africa (SSA) requires locally-led and setting-relevant evidence that should be driven by local investigators. However, there is a huge gap in the health research capacity to generate such evidence in most of SSA, particularly in Rwanda. With a changing focus and the willingness of investigators and funders from high-income countries (HICs) to support investigators and research from SSA, it is important to build strong, successful, and sustained partnerships. In this perspective, we describe the Einstein-Rwanda Research and Capacity Building Program (ER-RCBP), which represents almost two decades of a fruitful and sustained partnership that has contributed to the development of research physical and human resources in Rwanda. We have established a broad range of health research infrastructure that involves human resources, including training three pathologists, leadership and administrative personnel and structures, clinical research operations, laboratory capacity, and data collection and management systems, and are implementing a long-term plan to transfer most of the leadership to local investigators and the local lead institution. Our experience demonstrates that collaborations between high- and low-income countries can be leveraged to strengthen research capacity in SSA but that such efforts require putting in place structures and systems to ensure success. Building strong partnerships and collaborations, good leadership, empowering local teams, and having buy-in from national governments are key to achieving sustainable research capacity in SSA.